1996
DOI: 10.2105/ajph.86.9.1281
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative diseases: occupational occurrence and potential risk factors, 1982 through 1991.

Abstract: OBJECTIVES: To identify potential occupational risk factors, this study examined the occupational occurrence of various neurodegenerative diseases. METHODS: Death certificates from 27 states in the National Occupational Mortality Surveillance System were evaluated for 1982 to 1991. Proportionate mortality ratios were calculated by occupation for presenile dementia, Alzheimer's disease, Parkinson's disease, and motor neuron disease. RESULTS: Excess mortality was observed for all four categories in the following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
4
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(119 citation statements)
references
References 57 publications
4
109
4
2
Order By: Relevance
“…Lovell et al (82) showed that senile plaques in Alzheimer's Although the role of organochlorine compounds in neurodegenerative diseases has been less studied, increasing evidence suggests that organochlorines are involved, especially in Parkinson's disease. Schulte et al (84) report that incidences of Parkinson's disease, Alzheimer's disease, and ALS have increased in occupations involving exposure to pesticides and solvents. Specifically for Parkinson's disease, risk factors include rural living, well-water consumption, pesticide exposure, and exposure to solvents (85,86).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Lovell et al (82) showed that senile plaques in Alzheimer's Although the role of organochlorine compounds in neurodegenerative diseases has been less studied, increasing evidence suggests that organochlorines are involved, especially in Parkinson's disease. Schulte et al (84) report that incidences of Parkinson's disease, Alzheimer's disease, and ALS have increased in occupations involving exposure to pesticides and solvents. Specifically for Parkinson's disease, risk factors include rural living, well-water consumption, pesticide exposure, and exposure to solvents (85,86).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…5 Other studies have reported high incidence of sick leave due to nervous system diseases among boiler technicians in the American navy 9 and premature deaths due to neuromotor diseases among servicemen. 14 It was observed that servicemen who were communications technicians, electricians, technicians or operators of electronic equipment, carpenters, deck and aircraft equipment operators, maintenance personnel in general, cooks, hairdressers, those responsible for cleaning, orderliness and housekeeping services or musicians presented greater proportional death due to nervous system, genitourinary tract and digestive tract diseases than did the respective reference populations. There are only a few studies on occupational factors relating to servicemen's health, but they show that workers in the occupations of healthcare, general operations, naval engineering, maintenance, repairs and services, including those that belong to the marines, are at a greater risk of accidents and violent deaths, and infectious, respiratory and mental diseases, which are common among those working on ships.…”
Section: Discussionmentioning
confidence: 99%
“…Such exposure has, for example, been found to present an association with Alzheimer's disease and other neuromotor diseases among civilian workers who were operating radio and television stations and electric energy plants, and repairing telephone and electrical networks. 14 With regard to the effect of microwaves, studies on American servicemen who served during the period of the Korean War have presented data suggestive of a greater risk of nervous system diseases in the occupations of operating and repairing electrical, electronic and communications equipment. 12 Although there is no evidence regarding specific occupational risk factors among servicemen in relation to nervous system diseases, other types of exposure that are also common in the military working environment are associated with neuropathies, such as exposure to various metallic compounds, organochlorates, solvents and electromagnetic fields.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is very difficult to establish any causal link with a putative agent such as dental amalgam. In one study, occupational mercury exposure was related to an eightfold increase in risk of Parkinson's disease (Schulte et al 1996), but this is still a matter of debate and there is no scientifically sound report establishing a direct relation with dental fillings.…”
Section: Parkinson's Diseasementioning
confidence: 99%